Kinetic Studies On Anti-Oxidant Activity Vis-À-Vis Colour In Two Kashmir Honeys (Applied Biological Research, 2015)
The honey is generally heated to prevent crystallization and microbial  growth, however thermal treatment may affect honey qualities like  antioxidant activity, colour, etc. In this study the kinetics of antioxidant  activity change in correlation with honey colour has been studied.  Mustard and mixed floral honey samples were heated at 40, 50, 60, 70  and 80°C for 5 to 25 min. and changes in antioxidant activity measured  by DPPH method. The results showed that increase in temperature  increased kinetic constants so revealing favoured antioxidant activity.  The calculated activation energy using Arrhenius equation for  antioxidant activity at 40-80°C was 171.65 and 453.36 k calories mol-1 for mustard-based and mixed floral-based honey samples, respectively. Both the samples followed first order kinetics upto 60°C. At 70 and 80°C  the kinetic trend for mixed floral sample followed zero order kinetics.  The results demonstrated that increase in antioxidant activity was  significantly correlated with colour change in honey.
Keywords: Antioxidant activity; colour; honey; kinetics